Environmental controls on the thermal structure of alpine glaciers - N. J. Wilson; G. E. Flowers (The Cryosphere, 2013)
Water entrapped in glacier accumulation zones represents a significant latent heat contribution to the development of thermal structure. It also provides a direct link between glacier environments and thermal regimes. We apply a two-dimensional mechanically-coupled model of heat flow to synthetic glacier geometries in order to explore the environmental controls on flowband thermal structure. We use this model to test the sensitivity of thermal structure to physical and environmental variables and to explore glacier thermal response to environmental changes. In different conditions consistent with a warming climate, mean glacier temperature and the volume of temperate ice may either increase or decrease, depending on the competing effects of elevated meltwater production, reduced accumulation zone extent and thinning firn. For two model reference states that exhibit commonly-observed thermal structures, the fraction of temperate ice is shown to decline with warming air temperatures. Mass balance and aquifer sensitivities play an important role in determining how the englacial thermal regimes of alpine glaciers will adjust in the future.